Uji Tantang Bakteri Vibrio harveyi Pada Pasca Larva Udang Vaname (Litopenaeus vannamei) - Lestari, Ni Putu Tika; Julyantoro, Pande Gde Sasmita; Suryaningtyas, Endang Wulandari (Current Trends in Aquatic Science; Vol 1 No 1 (2018)DO - 10.24843/CTAS.2018.v01.i01.p15, 2018)
This research aims to determine the survival of Litopenaeus vannamei post larvae when challenged with various density of pathogenic Vibrio harveyi. The L. vannamei post larvae used in this study was obtained from Vannamei Broodstock  Center BPIUUK, Karangasem Bali. This research was conducted for two months, from April to May 2018 in fishery laboratory, Faculty of Marine Science and Fisheries, Udayana University by using complete randomized experimental design with four different V. harveyi density and three times repetitions. The study showed that the higher density of pathogenic V. harveyi resulted on the lower survival of L. vannamei post larvae. The highest density of V. harveyi 10 7 CFU/mL in treatment D resulted on 53±5.77% post larvae survival, while treatment A as control without addition of V. harveyi was still has survival of 100±0.00% at the end of experiment. The density 10 5 CFU/mL of V. harveyi (Treatment B) seems able to be tolerated by L. vannamei post larvae since the shrimp was still have high survival at this V. harveyi density. Further both V. harveyi density of 10 6 CFU/mL and 10 7 CFU/mL were not able to tolerated by the shrimp post larvae and lead to the high shrimp mortality. Although affected on shrimp survival, addition of V. harveyi have no significant effect to the weight of shrimp post larvae between treatments.